Metal recovering through recycling of printed circuit boards from computer devices using tabling and magnetic concentration methods - Triana, Tiara; Oediyani, Soesaptri; Suwandana, Rahman Faiz; Pradana, Adjie; Syaifara, Zuhrainis; Kusumaningtyas, Dewi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
The increasing human need for technology can have a negative impact on people's lifestyles which are becoming more consumptive. This causes the amount of electronic waste or e-waste to increase rapidly. Currently Printed Circuit Board is one of the wastes in e-waste which in 500 thousand tons of PCB contains around 150-200 thousand tons of metal. These metals are Cu, Pb, Zn, Au, Ag, Ni, Mn, Pd, and Fe. The metal contained in the PCB can be used as a secondary resource which can be further processed to produce valuable metals. The purpose of this research is to determine the particle size and prove whether the separation method is not effective in separating metals such as Cu and Ag from other metals. Based on XRF analysis to effectively separate Cu, Ag, and Au metals can use a particle size of 150μm with a Cu content of 78.673% and a particle size of 250μm with an Ag content of 0.083%. Separation is not effective to be carried out on PCB waste, this is because in the application of 1x magnetic separation, the Cu content is 80.51%. However, the type separation is less effective for the extraction of Ag metal. In separation using a shake table alone, the highest Ag content was obtained at 0.085%